Schooling, Nation Building, and Industrialization: A Gellnerian Approach - Esther Hauk; Javier Ortega (Institute for the Study of Labor (IZA), 2015)
We model a two-region country where value is created through bilateral production between masses and elites (bourgeois and landowners). Industrialization requires the elites to finance schools and the masses to attend them. Schooling raises productivity, particularly for matches between masses and bourgeois. At the same time, only country-wide education ("unified schooling") renders the masses mobile across regions. Alternatively, schools can be implemented in one region alone ("regional education") or the regionally dominant group can choose to implement schooling in its own region but refuse to share the costs/proceeds within the wider country-level group ("secession"). We show that schools are more likely to be set-up when the bourgeoisie dominates, but that this is not necessarily socially efficient. Unified schooling is always chosen if the identity of the dominant elite at the regional and country level is the same and/or the industrialization shock is sufficiently high. If instead the bourgeoisie is dominant in one region and landowners are dominant countrywise, the bourgeoisie of that region may promote the secession of the region, and this can be socially efficient. The model is shown to be consistent with evidence for 19th century France and Spain.
Keywords: D02; I2; N00; O14; 330; nation-building; education; industrialization